Effect of low inspired oxygen fraction on respiratory indices in mechanically ventilated horses anaesthetised with isoflurane and medetomidine constant rate infusion. (May 2016) - Taylor, A.H.; Seymour, C.J.
Highlights: Poor oxygenation can be a major problem in horses during anaesthesia. Low FiO2 is used to minimise atelectasis to improve respiratory function and oxygenation. Determination of invasive respiratory indices is difficult clinically, so non-invasive respiratory indices were substituted. Use of low FiO2 did not result in significant improvement in respiratory indices. The calculated F-shunt was not lower in the low FiO2 group. Abstract: Horses may become hypoxaemic during anaesthesia despite a high inspired oxygen fraction (FiO2 ). A lower FiO2 is used commonly in human beings to minimise atelectasis and to improve lung function, and previously has been shown to be of potential benefit in horses in experimental conditions. Other studies suggest no benefit to using a FiO2 of 0.5 during clinically relevant conditions; however, low FiO2 (0.65) is commonly used in practice and in a large number of studies. The present study was performed to compare the effect of a commonly used FiO2 of 0.65 versus 0.90 on calculated respiratory indices in anaesthetised mechanically ventilated horses in a clinical setting. Eighteen healthy Thoroughbred horses anaesthetised for experimental laryngeal surgery were recruited into a prospective, non-blinded, randomised clinical study. Before anaesthesia, the horses were randomly allocated into either low (0.65) or high (0.90) FiO2 groups and arterial blood gas (ABG) analysis was performed every 30 min during anaesthesia to allow for statistical analysis of respiratory indices. As expected, PaO2 was significantly lower in horses anaesthetised with a low FiO2, but was sufficient to fully saturate haemoglobin. There were no significant improvements in any of the other respiratory indices. There is no obvious benefit to be gained from the use of a FiO2 of 0.65 compared to 0.90 for mechanically ventilated Thoroughbred horses anaesthetised in lateral recumbency with isoflurane and a medetomidine constant rate infusion.